Sumulaskennan tarjoamat mahdollisuudet pilvilaskennan ongelmiin - Tikkanen, Topi (2018)
Utilizing cloud computing as a computing paradigm is becoming more and more common, but utilizing cloud comes with certain issues, such as increasing latency and distance. Fog computing is new computing paradigm, which can be utilized as a support for cloud computing to solve these issues. By conducting a literature review, this bachelor’s thesis provides answers to what issues lies on utilizing cloud computing and what fog computing offers to tackle these prob-lems. As a result of the literature review concludes that utilizing fog computing as a support for cloud computing provides solutions to almost all of the issues mentioned in the cloud computing literature, and to add to that fog computing also provides support for cloud computing to be utilized in many new ways.